Lymphocytic Pleural Effusion in a 16 Year Old Immunocompetent Girl − A Rare Etiology: Case Report - T.H. Deepak; Ananthu Joseph; S Santhakumar; J Venugopal (The Journal of Association of Chest Physicians)
This report presents a case study of a 16-year-old female patient with history of asthma who presented with left-sided consolidation and associated exudative lymphocytic pleural effusion that failed to respond to standard antibiotics and hence required decortication. Subsequent diagnostic evaluations revealed a diagnosis of Allergic Broncho Pulmonary Aspergillosis (ABPA), a condition that rarely involves pleural complications. Our case study serves to illustrate one such an instance of pleural involvement in ABPA.